Pengaruh Gaya Hidup Dan Penggunaan Uang Elektronik Terhadap Perilaku Konsumtif Warga Perumahan Al-Jazzera Kondangjaya Karawang - Aris Munandar; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
People's consumptive behavior is strongly influenced by several factors, such as lifestyle and the ease of use of electronic money. This study aims to determine the direct effect of lifestyle and electronic money on consumptive behavior and the indirect effect of lifestyle and electronic money on consumptive behavior. This research was conducted at Al-Jazzera Kondangjaya Housing, Karawang Regency. The number of samples taken was 72, from 246 existing populations. Data collection in this study was carried out through observation using a questionnaire. The data analysis technique used in this study was path analysis using the SPSS 24 application program. Based on the results of the analysis, it was found: (1) There is a strong correlation between lifestyle variables (X1) and electronic money (X2) with a positive correlation direction. (2) There is a partial influence of lifestyle variables (X1) on consumptive behavior (Y). (3) There is a partial influence of the electronic money variable (X2) on consumptive behavior (Y). (4) There is a significant simultaneous influence between lifestyle (X1) and electronic money (X2) on consumptive behavior (Y). Keyword: Lifestyle, Electronic Money, Consumptive Behaviour